2013
DOI: 10.1080/15389588.2013.792109
|View full text |Cite
|
Sign up to set email alerts
|

Side Impact PMHS Thoracic Response With Large-Volume Air Bag

Abstract: Two of the 3 PMHS sustained rib fractures despite low levels of thorax deflection. We attribute this finding to individual variability in subject injury tolerance. Other response parameters exhibited lower levels of variability and characterize PMHS response to a potentially beneficial side impact countermeasure. Supplemental materials are available for this article. Go to the publisher's online edition of Traffic Injury Prevention to view the supplemental file.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Examination of intrinsic variation among subjects (e.g. anthropometry and rib fracture tolerance) did not reveal any definite correlation between these factors and the injury outcome, and extrinsic factors, such as pre-impact posture, were not investigated , Shaw et al, 2014.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Examination of intrinsic variation among subjects (e.g. anthropometry and rib fracture tolerance) did not reveal any definite correlation between these factors and the injury outcome, and extrinsic factors, such as pre-impact posture, were not investigated , Shaw et al, 2014.…”
Section: Introductionmentioning
confidence: 98%
“…Two recent studies have reported the whole-body response of PMHS to side impact with a rigid wall and with an airbag (Shaw et al, 2014), including the six-degree-offreedom kinematics of skeletal structures in the PMHS. Injury outcomes varied substantially in these tests, ranging from no injury in two rigid-wall tests and one airbag test (no rib fractures) to moderate injury in one airbag test (2 rib fractures) to serious injury in one rigid-wall test and one airbag test (16 and 9 rib fractures respectively) ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations